THE EFFECTIVENESS OF USING HETEROTROPHIC BACTERIA TO RED NILE TILAPIA’S GROWTH (Oreochromis nilloticus) - Ismail Abdurrahman Siregar; F. Feliatra F. Feliatra; Dessy Yoswaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This study conducted in February-March 2019 at Marine Microbiology Laboratorium, Faculty of Fisheries and Marine, Riau University, Pekanbaru. The aim of this study is to know the effect of using heterotrophic bacteria to red nile tilapia’s (O. nilloticus) growth and to know the amount of heterotrophic bacteria in a pool. The study uses experimental method which is Completely Randomized Design (CRD).There are three treatments and three repetitions for each treatment. P1: Administration of heterotrophic bacteriaBacillus cereus 15ml/container, P2: Administration of heterotrophic bacteria Vagococcus fluvialis 15ml/container, P3: Administration of combining both heterotrophic bacteria(Bacillus cereus and Vagococcus fluvialis)15ml/container, and P4: Without the administration of heterotrophic bacteria. The heterotrophic bacteria is administered once a week. The result of this study shows that the best treatment is P3 by using the combination of both heterotrophic bacteria. Average weight growth is 5.38 grams, absolute weight growth is 3.03 grams, length increases 1.09 cm, spesific growth rate of fish is 14.45%. The parameter of water quality are temperature ranges between 26-280C, DO 3-5.75, pH 7.7-7.9 and ammonia 0.61-1.62 mg/L.Key Words:Heterotrophic Bacteria (B. cereus dan V. Fluvialis), Red nile tilapia(O. nilloticus